High‐Performance Perovskite‐Based Blue Light‐Emitting Diodes with Operational Stability by Using Organic Ammonium Cations as Passivating Agents. (26th October 2020) - Kim, Yun Cheol; An, Hee Ju; Kim, Do Hoon; Myoung, Jae‐Min; Heo, Ye Jin; Cho, Jeong Ho
Abstract: Blue emissive perovskites can be prepared by incorporating chlorine into bromine‐based perovskites to tune their bandgap. However, mixed‐halide perovskites exhibit intrinsic phase instability, particularly under electrical potential, owing to halide migration. To achieve high‐performance blue perovskite‐based light‐emitting diodes (PeLEDs) with operational stability, organic ammonium cations are used for passivating the anionic defects of the CsPbBr2 Cl film. Diphenylpropylammonium chloride (DPPACl), used as a passivating agent, successfully prevents the spectral instability of blue PeLEDs by passivating the Cl − vacancies. Consequently, the blue PeLED prepared with this passivating agent delivers excellent device performance with a maximum external quantum efficiency of 3.03%. Moreover, upon tuning the DPPACl concentration, the PeLED emits stably in the deep‐blue spectral region (464 nm) with a half‐life time of 420 s. Thus, the use of organic ammonium cation as a passivating agent is an effective strategy for developing high‐performance blue PeLEDs with operational stability. Abstract : The introduction of an appropriate passivating agent into the perovskite film is an effective technique for preventing the halide migration of mixed‐halide perovskites to develop high‐performance blue perovskite light emitting diodes (PeLEDs) with spectral stability. The PeLED with 60% diphenylpropylammonium chloride shows stable emission in the deep‐blue spectral region (464 nm) with a maximum external quantum efficiency of 1.92%.